Behavioral problems in children with asthma and their association – A cross-sectional study - Ramu, Somasekhar Ankanalli; Dakappa, Ahish; Suresh, Mithil Gowda; Mohamed, Safia; Anitha, D S; Akarsh, S; Vidyasagar, Dharmapuri (Indian Journal of Child Health, 2020)
Background: Asthma is a chronic illness involving the airways in the lungs and children are more susceptible. A strong link between asthma and psychiatric illnesses has been established. Hence, psychological factors govern its management. Objective: The objective of the study was to assess the self-esteem and behavior of asthmatic children. Materials and Methods: The cross-sectional study was conducted at the Department of Pediatrics of a Tertiary Hospital of South India. Asthmatic children between 6 and 16 years of age, diagnosed as mild to moderate, visiting the asthma clinic were included in the study. The respondents could either answer the questionnaire or point out their choices or indicate them verbally. Culture-Free Self-Esteem Inventory (CFSEI) by Battle (1981) was used for the study. Child Behavior Checklist by Achenback and Ederirock (1983) is designed to record in a standardized format the behavioral problems and social competencies of children, as reported by parents/guardians. Results: A total of 70 children were enrolled in the study. There were 30 children each in the case and control group, with regular follow-ups to the clinic. The majority of the children belonged to the age group of 10–13 years (63.3%) in the case and 10–14 years (63.03%) in the control group. Among the cases, about 50% had at least 3 wheezing episodes. Among the number of inpatient admissions, 14 were admitted once, four were admitted twice, and one child had three admissions. The school absenteeism in case varied from 1 to 6 weeks per academic year. Mean self-esteem scales for boys were 10.36 in case and 13.05 in control (p